Correction: Lin et al. Research on Machine Learning Models for Maize Hardness Prediction Based on Indentation Test. Agriculture 2024, 14, 224 - Haipeng Lin; Xuefeng Song; Fei Dai; Fengwei Zhang; Qiang Xie; Huhu Chen (Agriculture)
In the original publication [...]